STRATEGIC ANALYSIS FOR MSME BUSINESS MODEL INNOVATION WITH PRODUCT-SERVICE SYSTEM - Siti Maria Ulfah; Nanang Alamsyah; Mohammad Rachman Waluyo; Wendy Febrianty Mardhiyah (LPPM Universitas Malikussaleh, 2025)
This study examines a cassava chips MSME in Gunung Sindur to identify the business model innovation gap between pure product orientation and service integration, as well as to formulate a realistic Product–Service System (PSS) configuration to enhance competitiveness. Using a qualitative-case study approach, data were collected through in-depth interviews with the owner, field observations, and structured questionnaires, and then analyzed using a PSS matrix to determine the existing position and potential for service development. The results show that the business is still operating as a pure product, but the owner wants to add services such as delivery, consignment sales, and a mini-marketplace. Among the alternatives evaluated, Product Pooling emerged as the most feasible option because it can add value and expand market reach without requiring significant investment; meanwhile, delivery services and a pay-per-unit scheme are not yet feasible due to limited resources and infrastructure. These findings provide a practical basis for developing PSS strategies for local food MSMEs by emphasizing collaboration among players and enhancing service capabilities.